Towards a symbol literacy approach in the education of children. Issue 2 (3rd April 2018) - Gellel, Adrian-Mario
Abstract: Children enter a world that is full of symbols, most of which have become inaccessible. This is true not only because of a positivistic attitude that views analogical truth as nonsensical, but also because of the fragmentation that we experience. This situation is impoverishing children's awareness, connectedness as well as their ability to access and express existential concerns and the answers different generations have tried to provide. It is for this reason that children need to learn a variety of symbols and the 'grammar' of how they form meaning. A symbolic literacy approach not only helps them to read symbols but also enables them to formulate meaning and to connect with the deeper reality and facilitates their ability to transcend physical reality. The paper will also refer to the development of an interdisciplinary pedagogy and its implementation through a project that is being done in collaboration with Maltese primary schools.